ISLAMIC FINANCIAL BEHAVIOUR AS A DRIVER IN SHAPING HOUSEHOLD FINANCIAL WELL-BEING - Rizky Firmansyah; Dediek Tri Kurniawan; Vianca Annabel Rasiady (Faculty of Economics Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
This study examines how Islamic financial behaviour moderates the effects of religiosity, Islamic financial literacy, and financial stress on financial well-being. Data from 247 respondents were collected and analyzed using SEM-PLS. It was found that Islamic financial literacy improves Islamic financial behaviour; however, it had no significant effect on financial well-being. The impact of religiosity is felt on Islamic financial behaviour and not on financial well-being. Financial stress is considered detrimental to financial well-being, whereas Islamic financial behaviour is negligible. Islamic financial behaviour is positively associated with financial well-being. Hence, there is a need to develop Islamic financial literacy and religiosity to positively influence Islamic financial behaviour and increase the financial well-being of Muslim households in Indonesia